2011
DOI: 10.1007/s13105-011-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-rich date palm fruit extract inhibits oxidative stress and nephrotoxicity induced by dimethoate in rat

Abstract: Recent investigations have proved the crucial role of nutritional antioxidants to prevent the damage caused by toxic compounds. In this study, the antioxidant effect of date palm fruit extract on dimethoate-induced oxidative stress and nephrotoxicity in rat is investigated and compared with the effect of the well-known antioxidant vitamin C. Male Wistar rats were randomly divided into six groups of ten each: a control group (C), a group that received dimethoate (20 mg/kg body weight) (D), a group given Deglet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 65 publications
5
22
1
Order By: Relevance
“…Also, Al-Qarawi et al [39] reported that administration of the extracts of the flesh and pits of palm date caused significant improvement in serum creatinine and urea concentrations and the proximal tubular damage in a gentamicin-induced nephrotoxicity in rats. Moreover, Saafi-Ben Salah et al [17] showed that aqueous extract of Deglet Nour cultivar has improved serum creatinine and urea and attenuated the histopathological damage induced by dimethoate in kidney of rats. Also, Ali and Abdu [40] showed that the aqueous date extract of Ajwa cultivar has improved the histopathological change induced by Ochratoxin (A) in renal distal and proximal tubules.…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Al-Qarawi et al [39] reported that administration of the extracts of the flesh and pits of palm date caused significant improvement in serum creatinine and urea concentrations and the proximal tubular damage in a gentamicin-induced nephrotoxicity in rats. Moreover, Saafi-Ben Salah et al [17] showed that aqueous extract of Deglet Nour cultivar has improved serum creatinine and urea and attenuated the histopathological damage induced by dimethoate in kidney of rats. Also, Ali and Abdu [40] showed that the aqueous date extract of Ajwa cultivar has improved the histopathological change induced by Ochratoxin (A) in renal distal and proximal tubules.…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 99%
“…AlQarawi et al [39] suggested that the nephroprotective action of extracts of the flesh and pits of Phoenix dactylifera in gentamicin-induced nephrotoxicity attributed to the antioxidant components of date such as melatonin, vitamin E and ascorbic acid. Also, Saafi-Ben Salah et al [17] showed that date aqueous extract of Deglet Nour cultivar has attenuated lipid peroxidation and improved antioxidant defense system in dimethoate-induced nephrotoxicity. The protective effect of aqueous date extract to their high amounts of antioxidant substances such as polyphenols, trace elements, and vitamin C [13,[44][45][46].…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 99%
See 1 more Smart Citation
“…Producers, pesticide workers, and farm owners are the basic risk groups of dimethoate exposure [3] . Previous studies indicate that dimethoate leads to oxidative stress via production of free radicals and induction of lipid peroxidation [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement in the content of MDA might have resulted from an increase in reactive oxygen species, as a result of stress in rats exposed to TCA toxication. Also, an elevation of MDA results by superoxide overproduction, after which dismutation produces single oxygen and H 2 O 2 , easily converted later into the reactive OH, which starts free-radical chain reactions of lipid peroxidation (Salah et al, 2012). Furthermore, it has been examined that petroleum diethyl ether extracts of Sideritis sp.…”
Section: Enzymatic Antioxidant Status Mda and Gsh Level In Liver Andmentioning
confidence: 99%